From the Editor - Jeri W Dunkin (Rural Nurse Organization; Binghamton University, 2012)
As we put the final touches to this issue I came to realize that the Journal has become quite stable in the number of articles included in each issue as  well as the numbers of editorial columns.  In reviewing the history I found that we had published 97 articles and 91 editorial columns or between 4 and 5 of each per issue.  Interestingly enough that number stayed about the same from Volume 1 through  Volume 9.  These articles covered a wide range of topics and came from several different countries as well.  It clearly demonstrates that while rural nursing is very diverse, it is at the same time the issues across countries remain the same.  Those of access, resources, and geographic barriers.  These are the barriers that all rural nurses face.  That commonality of diversity is what moved me to start the journal originally and I hope that it has provided rural nurses throughout the world with a resource to use for comparison of their issues to those of  others and examples of approaches taken to mitigate those issues and research on topics  pertinent to practice.  I would welcome any comments or suggestions on how we might improve the Journal and its usefulness to you, the nurse caring for rural populations wherever that may be.  I  can be contacted by email at rural.nurse.org@gmail.com.